Trichotillomania – therapeutic possibilities - Nemeczek, Sylwia; Merkisz, Konrad; Walczak, Klaudia; Walczak, Patrycja; Zdun, Sylwia; Grzybowski, Jakub; Marciniak, Agnieszka; Grzywna, Natalia; Jaskuła, Karolina; Orłowski, Władysław (Journal of Education, Health and Sport, 2023)
Introduction: Trichotillomania is a mental disorder in which the patient persistently and recurrently pulls out his own hair, which results in varying degrees of hair loss. This causes considerable suffering and impairs quality of life, but patients rarely seek specialist help. It affects 0.5–3% of the general population, but data may be underestimated due to low reporting. Aim of the study: The aim of our study is to summarize the current state of knowledge on the treatment of trichotillomania. Materials and methods: The literature available in the PubMed and Google Scholar database was reviewed using the following keywords: "trichotillomania", "trichophagia", "trichobeozar", "trichotillomania treatment". Results: Treatment of TTM is difficult and involves many methods. The division of therapeutic methods focuses mainly on psychotherapy and pharmacological treatment. The greatest effectiveness is attributed to cognitive-behavioral therapy, especially habit reversal training. Medications can help reduce symptoms, especially in the presence of other disorders, e.g. depression, anxiety disorders. Conclusions: Trichotillomania contributes to significant suffering and negatively affects functioning in social and professional life. The basis of its treatment is psychotherapy, but there are many reports on the effectiveness of selected drugs (SSRIs, clomipramine, antipsychotics, N-acetylcysteine, naltrexone, lamotrigine, bupropion, dronabinol, inositol), but they require further research on a larger group of patients.